2015
DOI: 10.1039/c4ta06557c
|View full text |Cite
|
Sign up to set email alerts
|

Computational studies on structural and electronic properties of functionalized MXene monolayers and nanotubes

Abstract: This work discloses that the electronic properties of MXenes can be controlled by rolling layers into 10 different types of nanotubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(73 citation statements)
references
References 50 publications
2
71
0
Order By: Relevance
“…Many opportunities and challenges exist simultaneously. These include the preparation of bare MXenes; the exfoliation of new MXenes; the studies on their 1D forms [76,77]; the practical measurements of their magnetic, elastic, and optical properties; and their potential applications. All await further research efforts and increased understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Many opportunities and challenges exist simultaneously. These include the preparation of bare MXenes; the exfoliation of new MXenes; the studies on their 1D forms [76,77]; the practical measurements of their magnetic, elastic, and optical properties; and their potential applications. All await further research efforts and increased understanding.…”
Section: Discussionmentioning
confidence: 99%
“…The surface of MXene is exposed to metals atoms and carbon atoms are atomically attached to the metal atoms. It has already been shown that the surface functionalization has a major impact both on structural and electronic properties of MXenes [1,2,[23][24][25][26][27][28]. For example, surface termination significantly reduces the specific capacity [29] and may * Electronic address: gberdiyorov@qf.org.qa † Electronic address: mmadjet@qf.org.qa result in band gap opening in the band structure [23].…”
Section: Introductionmentioning
confidence: 99%
“…17 However, recent density-functional theory calculations predict that both structural and electronic properties of MXenes are strongly affected by surface functionalization. [18][19][20][21][22][23] For example, the surface termination results in sizable changes in the structural properties and stability of MXenes. 21 Some of the initially metallic MXenes can become semiconductors with a small energy band gap after the surface passivation.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23] For example, the surface termination results in sizable changes in the structural properties and stability of MXenes. 21 Some of the initially metallic MXenes can become semiconductors with a small energy band gap after the surface passivation. 20 Electronic transport properties of the MXene materials can be significantly increased by specific termination of the MXene surfaces.…”
Section: Introductionmentioning
confidence: 99%